IMPROVING COLLEGE STUDENT RETENTION : New Developments in Theory, Research, and Practice - Reason, Robert Dean; Braxton, John M. (Stylus Publishing, LLC, 2023)
"Overall retention rates have stagnated and differential retention rates by race and ethnicity have persisted. This edited book examines how higher education institutions, researchers, and policy makers can work to improve retention rates by critically examining the current state and future directions of retention research"--